2021
DOI: 10.3390/ijms22126257
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Eight Fusarium graminearum Strains with Contrasting Aggressiveness Reveals an Expanded Open Pangenome and Extended Effector Content Signatures

Abstract: Fusarium graminearum, the primary cause of Fusarium head blight (FHB) in small-grain cereals, demonstrates remarkably variable levels of aggressiveness in its host, producing different infection dynamics and contrasted symptom severity. While the secreted proteins, including effectors, are thought to be one of the essential components of aggressiveness, our knowledge of the intra-species genomic diversity of F. graminearum is still limited. In this work, we sequenced eight European F. graminearum strains of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 124 publications
(170 reference statements)
2
23
0
Order By: Relevance
“…Taking advantage of different F. graminearum strains and wheat host cultivars, this study identified the in planta expression of 840 unique fungal genes harboring effectorassociated features (i.e., genes encoding secreted proteins and differentially expressed during the FHB infection), including nine new accessions not included in the reference PH-1 genome. These represent almost 5% of F. graminearum pangenome and more than 35% of its putative pansecretome [49].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking advantage of different F. graminearum strains and wheat host cultivars, this study identified the in planta expression of 840 unique fungal genes harboring effectorassociated features (i.e., genes encoding secreted proteins and differentially expressed during the FHB infection), including nine new accessions not included in the reference PH-1 genome. These represent almost 5% of F. graminearum pangenome and more than 35% of its putative pansecretome [49].…”
Section: Discussionmentioning
confidence: 99%
“…Because previous comparative genomic studies demonstrated that F. graminearum putative pathogenicity-related genes were located in variable regions of the genome [49,54,55], the distribution of our core effectome on F. graminearum genome was studied (Supplementary Table S4). At both inter-and intrachromosomal level, spatial distribution of the core effector genes was uneven (Figure S3).…”
Section: Localization In the Fast-evolving Subgenomementioning
confidence: 99%
See 2 more Smart Citations
“…The results of the current study also provide evidence for positive selection of the ancestral Trichoderma tri5 during its divergence from tri5 in other fungi ( Figures 4 , 5 ). There is evidence for positive selection of other secondary metabolite biosynthetic genes in fungi ( Massonnet et al, 2018 ; Alouane et al, 2021 ). In these other fungi, the selection was attributed to adaptation to environmental changes.…”
Section: Discussionmentioning
confidence: 99%